The right to access urban green spaces: an (in)equality issue in the contemporary societies - Vidal, Diogo Guedes (2019)
World's population living in cities is expected to rise from around 54% to around 66% by 2050 (Maia, 2014, UN, 2014). Urban green spaces (UGS) could be assumed as a link between nature and urban life. Far from being only understood as passives spaces of leisure and socialization, UGS are endowed with unequivocal potentialities in the promotion of a more inclusive and participative society. Many studies had focused on this aspect, sometimes neglecting the beneficial side that directly or indirectly contributes to the improvement of life quality of individuals. In this way, UGS have the power to rejuvenate urban network and surrounding residential quality, improving human health (WHO, 2016; Kuo, 2015; Sturm & Cohen, 2014; Lee &Maheswaran, 2010), mitigate air pollution and noise (WHO, 2017) and minimizing the impacts caused by climate change (WHO, 2017; Kabischet al., 2016; Mathey et al., 2011). This communication intends to share some preliminary reflections about a research with the main goal to understand if the cities are responding to population needs related to social and environmental challenges, taking into account the role of UGS in the city of Porto. Access to UGS should be understood as a universal right, as way of practicing citizenship. For this reason, it is important to analyse if exists or not equal access to this spaces, being a reflex of how society is organised. The importance of this reflection is aligned with the 11th goal of the 2030 agenda for sustainable development with the target by 2030 to provide universal access to safe, inclusive and accessible, green and public spaces, in particular for women, children, older persons and persons with disabilities(UN, 2015). An equal access to UGS as a right could improve social interaction and community cohesiveness, as well as contribute to a more sustainable society.